Intestinal coccidiosis infection in domestic rabbits - Sivajothi, S; Reddy, B. Sudhakara; Rayulu, V. C. (International Journal of Biological Research, 2014)
The present study reports about the intestinal coccidiosis in a commercial rabbit farm. Seven New Zealand white rabbits were died in a commercial rabbit farm in Tirupati during the month of August. All the rabbits had signs of anorexia, diarrhea, dullness and weakness. Rabbits were necropsied and collected the intestinal contents for laboratory examination. Up on post mortem examination, hyperemic and oedematous intestinal mucosa was noticed. Oocysts of Eimeria spp. were detected in the faeces of all the rabbits. The collected oocysts were transferred into 2.5% aqueous potassium dichromate solution for sporulation. Faecal samples were examined by modified McMaster technique to determine oocyst counts which had ranged from 13,200 to 16,400. Keywords: Intestinal Coccidiosis, OPG, Rabbits, Sporulation.